Effect of rootstocks on growth, yield and fruit quality attributes of sweet orange (Citrus sinensis) cv. Sathgudi (Indian Journal of Arid Horticulture, 2018)
The plant growth, yield and fruit quality attributes of 'Sathgudi' sweet orange (Citrus sinensis (L.) Osbeck) on four  rootstocks were evaluated under semi-arid conditions of central Gujarat at Central Horticultural Experiment Station (ICAR CIAH, Bikaner), Godhra during the year 2016-2017 and 2017-2018. Results showed that various rootstocks had significant effect  on growth, yield, fruit weight and quality of Sathgudi sweet orange. The highest plant height (1.50 m), root stock girth (17.20 cm),  scion girth (16.30 cm), plant spread (1.40 m & 1.35 m) and tree volume (1.48 m ) were observed with Rangpur lime rootstock closely followed by rough lemon. The fruit weight and yield were also affected by different rootstocks. Trees on 'Carrizzo'  citrange had lower fruit weight and yield than those budded on to the other rootstocks. Significantly, the maximum fruit weight  (170.20 g), yield (8.5 kg/plant), juice percent (42.12 %), TSS (12.0 Brix), TSS and acid ratio (8.95), total sugar (5.70%) and  vitamin C (58.90 mg/100g) were found in Sathgudi trees budded on to Rangpur lime.
Keywords: Orange; rootstock; growth; yield; quality